Penyuluhan dan Pelatihan Pembuatan Arang Briket dari Biomassa di Gereja Santo Yosef Ngawi - Setyadi Setyadi; Suratno Lourentius; Lourentius Hadi Santosa; Yuliati Yuliati; Widya Andyardja Weliamto (LPPM, Universitas Katolik Widya Mandala Surabaya, 2021)
Making charcoal briquettes from biomass for socio-economic development activists in Kevikepan Ngawi is way to solve the problem of waste from biomass in rural areas. Therefore, the waste problem and its solutions need to be socialized and implemented according to the capabilities of the local community. Then there was an education about how to process biomass into charcoal briquettes. The stages that were carried out includ-ed the preparation and implementation stages. The preparatory stage is to visit the area where the event is held at the Catholic Church of Santo Yosef Ngawi in order to confirm the event and prepare the method that will be carried out. The implementation stage is in the form of counseling which will be held on Saturday, July 28 2018 at 09.00 - 13.00. The activity was held at the Santo Yusup Ngawi Parish and the activity was attended by 57 members of the Kevikepan Ngawi community. The essence of the event at the implemen-tation stage is in the form of an explanation and demonstration of how to process waste by means of the briquette charcoal making method. The results of monitoring from the Unika Widya Mandala Surabaya community service team are that counseling and train-ing on making charcoal briquettes is new knowledge that can be done and developed because in Ngawi there is a lot of waste from biomass.